Time‐use for the iGeneration: A person‐centered approach - Vernon, Lynette (Wiley Online Library, 2019)
This study used a person‐centered approach to identify classes of adolescents characterized by unique patterns of time‐use including traditional activities (paid work, homework, television, physical activity) and technological activities (gaming, social networking, Internet) and examined the relation to developmental outcomes (extracurricular activities, sleep, and academic attainment). A sample of 948 mainly Caucasian (56.6%) adolescents (43% male; M age = 15.4 years) from 28 high schools were surveyed. Time‐use classes were derived using latent class analysis. Four classes of adolescent time‐use were identified: Analoggers, Gamers, Digital All‐rounders, and Social Networkers. Classes differentially associated with developmental outcomes, controlling for gender and socioeconomic status. The Gamers (15.7%; active in one domain) were more likely to be males, with the lowest engagement in extracurricular activities and lowest academic attainment when compared to other groups. The Digital All‐rounders (24.9%; engagement in multiple domains) obtained the lowest amount of sleep, however, on average, participated in sport, and had an academic self‐concept of similar levels to Analoggers (40.3%; highly engaged in traditional activities, less engaged in the technological domain). Social Networkers (19.1%), on average, heavily invested in one technological activity at the expense of other activities, having the poorest outcomes alongside Gamers. Examination of typologies of adolescent time‐use can support understanding of technology‐related activity patterns and associations with extracurricular activities, sleep and academic attainment. The person‐centered approach enables us to disentangle contradictory findings related to adolescent technology use, particularly when comparing those who engage across a range of activities compared to those only engaged in one domain.